The Effect of the Reading Concept Map Reciprocal Teaching (Remap RT) Learning Model on Students' Concept Understanding and Learning Interest in the Nervous System Sub-Material - Alfian, Rizal Nur; Alamsyah, Muhammad Radian Nur; Sukmawati, Ika (Universitas Islam Negeri Walisongo Semarang, 2024)
This research aims to determine the effect of the reading concept map reciprocal teaching (Remap RT) learning model on students' understanding of concepts and learning interest in the nervous system sub-material. This type of research is quantitative research with a quasi experiment type nonequivalent control group design. The population in this study was all students in class XI MIPA at SMA IT Ihsanul Fikri with the samples used are class XI MIPA 2 as the control class and class XI MIPA 3 as the experimental class. The results of the research show that the hypothesis analysis on the posttest score for students' conceptual understanding has a significance value of 0.002 (Sig.0.05). The experimental class also had a better average score than the control class. Then in the students' learning interest data, it is known that the results of the hypothesis analysis show a significance value of 0.000 (Sig.0.05). The experimental class has a higher average value of interest in learning than the control class. In conclusion that there is an effect of the Remap RT learning model on students' understanding of concepts and learning interest in the nervous system sub-material.